Quo Vadis Perjuangan Perempuan Indonesia Dalam Masa Pandemi Covid-19 - Fridiyanti, Yulita Nilam (JURNAL LANSKAP POLITIK, 2022)
This paper aims to determine the role of women other than as wives and mothers of women during the COVID-19 pandemic at home. By using qualitative research methods with literature studies. Collecting data using articles, journals, books and others through the media. The results of this study indicate that women in the family have an important role, namely as wives for their husbands and as mothers for their children. And at the time of COVID-19, women were not only required to play a role, both of them were also required to be teachers of children at home during the pandemic. So women play a role from guiding the family while at home to being the frontline healing Covid-19 as doctors and nurses. In addition, women are also in a vulnerable position to experience domestic violence. The increase in cases of gender-based violence during the Covid-19 pandemic is quite worrying because it can directly reduce the fighting power of Indonesian women both physically and mentally in fighting Covid-19. Therefore, it is necessary to have high appreciation, protection, and education for women by increasing trust in women in handling Covid-19.